2019
DOI: 10.4018/978-1-5225-7906-9.ch012
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Values and Knowledge on Green Products Purchase Intention

Abstract: Marketing managers keenly seek to understand the green market. However, insufficient information on how to foster consumers' green behavior is slowing the growth of green markets and becoming a barrier for firms when communicating strategies for effectively promoting green products. Therefore, this chapter attempts to examine the impact of environmental knowledge and cultural values on consumers' green purchase intentions. A survey was administered and a total of 200 valid questionnaires were obtained. Structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…TPB (theory of planned behavior) has been used in several studies that are related to environmental or green behavior such as the usage of green e-books [11], predicting green behavior [12,13], and the willingness to buy appliances that save energy consumption [14]. Another study of waste separation behavior was conducted in Malaysia that utilized the TPB and showed that subjective norms, attitudes, and perceived behavior control positively affect waste separation behavior among households in Malaysia [15].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…TPB (theory of planned behavior) has been used in several studies that are related to environmental or green behavior such as the usage of green e-books [11], predicting green behavior [12,13], and the willingness to buy appliances that save energy consumption [14]. Another study of waste separation behavior was conducted in Malaysia that utilized the TPB and showed that subjective norms, attitudes, and perceived behavior control positively affect waste separation behavior among households in Malaysia [15].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…With this value, it means that the respondents significantly agree that the unavailability of information regarding the mechanisms, benefits, and rules for managing used cell phones will hinder their desire to collaborate in handling used cell phones. This result also occurred in the use of renewable energy in food production [38], in the green market in China [39], in the production of recycled concrete aggregates [40], and in the promotion of green products [41].…”
Section: Discussionmentioning
confidence: 99%
“…Makul et al (2021) [40] argued that the lack of information on longevity and sustainability as a serious problem concerning recycled concrete aggregates production. Insufficient information is one of the barriers to promoting green products [41].…”
Section: Unavailability Of Informationmentioning
confidence: 99%
“…Previous research on environmental behaviour and behavioural intention had frequently disregarded subjective standards and eliminated them from analysis [40][41][42]. Subjective norms have a favourable effect on the intake of various foods and beverages including alcohol and fast-food consumption [28], fish burger consumption [43], fish consumption [44], genetically-modified tomatoes [45], and green products [46][47][48].…”
Section: Subjective Normsmentioning
confidence: 99%